Old Babylonian Legal and Administrative Texts from Philadelphia - van Lerberghe, Karel (1986)
in collaboration with Marten Stol and Gabriela Voet; 101 texts, mainly from the "Sippar region"; no. 50 (CBS 1219) most probably comes from Kish.